Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.30647/trj.v6i2.144
|View full text |Cite
|
Sign up to set email alerts
|

Wellness Tourism Model in Recovery Sector Tourism in Belitung during the New Normal Period

Abstract: Belitung Regency is the district that determines tourism as the main sector. Development tourist experiences drop in aspect economy, employment, and tax for an area with the Covid-19 pandemic. This research focuses on and aims to analyze how the Wellness Tourism model in the recovery of tourism in Belitung Regency during the new normal period. The results showed that model Wellness Tourism starts from the application of Wellness Tourism indicators, namely (1) High Standard Sanitation; (2) High Standard Securit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…This imperative arises from the need to sustain growth and ensure tourists experience a profound sense of immersion, spirituality and community engagement. The analysis of stakeholders underscores the pivotal role played by entities situated in quadrant II (key players) are groups that have high influence and interest, in steering the recovery of Bangka Belitung tourism amidst the new normal (Valeriani et al, 2021). Notably, the government, stateowned enterprises (Badan Usaha Milik Negara), academics and tourism-awareness groups emerge as the stakeholders with the most significant impact (Valeriani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This imperative arises from the need to sustain growth and ensure tourists experience a profound sense of immersion, spirituality and community engagement. The analysis of stakeholders underscores the pivotal role played by entities situated in quadrant II (key players) are groups that have high influence and interest, in steering the recovery of Bangka Belitung tourism amidst the new normal (Valeriani et al, 2021). Notably, the government, stateowned enterprises (Badan Usaha Milik Negara), academics and tourism-awareness groups emerge as the stakeholders with the most significant impact (Valeriani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The research findings pertaining to the inner wellness tourism model for the recovery of tourist activities on Bangka Island during the new normal have revealed that the wellness tourism model in Bangka Regency encompasses the following indicators: (a) high standard sanitation; (b) high standard security; (c) staycation; (d) niche tourism; (e) private travel tours; (f) virtual tourism. Each of these indicators is intricately linked to aspects such as transportation, food, activities, health, service promotion, rooms, management and environment (Valeriani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A staycation can be considered one of the indicators of wellness tourism as it provides immediate effects on perceived stress, recovery, and well-being (Miao et al, 2021). Moreover, it has become a part of a new normal of tourism in the COVID-19 era, where the tourist emphasises cleanliness and health and safety, such as social distancing while travelling, wearing face masks and sanitising hands (Valeriani et al, 2022). While recent studies have explored the positive impacts of staycation on the hospitality industry during the pandemic (Nair et al, 2022;Yan et al, 2022), little has been done to understand the association of staycation to wellness tourism during and after the COVID-19 pandemic (Lin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%